2012
DOI: 10.1007/s13238-012-2021-x
|View full text |Cite
|
Sign up to set email alerts
|

The potential link between PML NBs and ICP0 in regulating lytic and latent infection of HSV-1

Abstract: Herpes simplex virus type 1 (HSV-1) is a common human pathogen causing cold sores and even more serious diseases. It can establish a latent stage in sensory ganglia after primary epithelial infections, and reactivate in response to stress or sunlight. Previous studies have demonstrated that viral immediate-early protein ICP0 plays a key role in regulating the balance between lytic and latent infection. Recently, It has been determined that promyelocytic leukemia (PML) nuclear bodies (NBs), small nuclear sub-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 130 publications
(120 reference statements)
0
16
0
Order By: Relevance
“…In addition to their roles in telomere stability, PML-NBs have antiviral defense functions (36), (35). In contrast to many other viruses including HSV, CMV, EBV and HHV-8, HHV-6A/B infection does not lead to the dispersal of PML-NBs but rather to PML-NBs coalescence (38), (66), (67), (68), (33). Whether this affects antiviral functions of PML-NBs remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their roles in telomere stability, PML-NBs have antiviral defense functions (36), (35). In contrast to many other viruses including HSV, CMV, EBV and HHV-8, HHV-6A/B infection does not lead to the dispersal of PML-NBs but rather to PML-NBs coalescence (38), (66), (67), (68), (33). Whether this affects antiviral functions of PML-NBs remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Some viruses have developed ways to overcome this antiviral mechanism by degrading or manipulating PML-NBs. For example, herpes simplex virus 1 (HSV-1) encodes the E3 ligase ICP0 that conjugates ubiquitin to PML and induces its degradation (37), (38). Human cytomegalovirus (hCMV) IE1 de-SUMOylates PML-NBs resulting in PML redistribution (39).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been shown that PML-NBs have role in the repression of HSV-1 infection in the absence of functional ICP0 and they may be involved in regulating lytic and latent infection of HSV-1 (Wang et al, 2012). PML-NB protein has been shown to interact with the EBV protein SM and increase the stability of lytic EBV transcripts (Nicewonger et al, 2004).…”
Section: 8019 Promyelocytic Leukemia Gene Functions and Roles In Tummentioning
confidence: 99%
“…PML NBs regulate multiple cellular functions, including antiviral responses (1)(2)(3)(4). Many RNA and DNA viruses, including herpesviruses from all three (alpha, beta, and gamma) subfamilies have correspondingly evolved different mechanisms to modulate PML NBs or PML NB-associated proteins (e.g., Sp100 and Daxx) during both lytic and latent infection (3)(4)(5)(6). For example, herpes simplex virus 1 (HSV-1) ICP0 (7,8), Epstein-Barr virus (EBV) EBNA1 (9), Kaposi's sarcoma-associated herpesvirus (KSHV) LANA2 (10), and murine gammaherpesvirus 68 (MHV68) ORF75c (11,12) target the PML protein for degradation through a proteasome-dependent pathway.…”
mentioning
confidence: 99%